2021
DOI: 10.1080/21655979.2021.1933301
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the molecular targets and mechanisms of xuebijing injection for the treatment of COVID-19 via network pharmacology and molecular docking

Abstract: Xuebijing Injection have been found to improve the clinical symptoms of COVID-19 and alleviate disease severity, but the mechanisms are currently unclear. This study aimed to investigate the potential molecular targets and mechanisms of the Xuebijing injection in treating COVID-19 via network pharmacology and molecular docking analysis. The main active ingredients and therapeutic targets of the Xuebijing injection, and the pathogenic targets of COVID-19 were screened using the TCMSP, UniProt, and GeneCard data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…To fully evaluate the curative effects and mechanisms of Quercetin in treating CRF scientifically, the present study established a CRF rat model and intragastrically administered Quercetin to determine its effects. We constructed a regulatory network of SQJZJN-Quercetin-PIK3R1-CRF in a network pharmacological approach, investigated the target functions and molecular regulatory mechanisms to clarify the mechanisms of Quercetin on alleviating or delaying renal fibrosis [ 10 ] . The present study aimed to explore the mechanisms in the incidence and development of CRF, the clinical efficacy of SQJZJN and Quercetin, and the mechanisms of alleviating renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…To fully evaluate the curative effects and mechanisms of Quercetin in treating CRF scientifically, the present study established a CRF rat model and intragastrically administered Quercetin to determine its effects. We constructed a regulatory network of SQJZJN-Quercetin-PIK3R1-CRF in a network pharmacological approach, investigated the target functions and molecular regulatory mechanisms to clarify the mechanisms of Quercetin on alleviating or delaying renal fibrosis [ 10 ] . The present study aimed to explore the mechanisms in the incidence and development of CRF, the clinical efficacy of SQJZJN and Quercetin, and the mechanisms of alleviating renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Other clinical studies also found that the NF- κ B activity was increased in NASH patients. AKT regulates NF- κ B signal transduction through phosphorylation of IKK α , which leads to the degradation of I κ B [ 34 ]. This process releases NF- κ B from the cytoplasm into the nucleus to further regulate the expression of downstream target genes and finally mediate multiple pathological processes such as liver inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 disease caused by SARS-CoV-2, which spreads worldwide from Wuhan, China, and caused %2 of the death of COVID-19 patients as an average mortality rate worldwide, is a member of the beta coronavirus family (1,3,(11)(12)(13). It is reported that during the pandemic process, a lot of scientific researches was carried out, in particular, the molecular and biological mechanisms of COVID-19 as well as diagnosis and treatment (14)(15)(16)(17)(18)(19)(20)(21)(22). Analyzing the literature related to COVID-19 helps us to evaluate the pathophysiologic mechanism of the disease and understand its progression.…”
Section: Discussionmentioning
confidence: 99%